ANALISIS PENGARUH KUALITAS AUDIT DAN REAL EARNING MANAGEMENT TERHADAP LABA OPERASIONAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (PERIODE 2013-2016) (JURNAL EKONOMI AL-KHITMAH, 2019)
This study aims to test empiricall influence of audit quality and real earning management toward operational profit in the Manufacturing company registered in BEI period 2013-2016. The sampling technique used purposive sampling method which resulted in a sample of 40 sample. Researchers used multiple linear regression techniques analysis. The results showed that: 1). Audit quality does not have affect toward operational profit; 2). Real earning management has affect toward operational profit